Intel® Cluster Checker Multi-Language API - Guzmán, Mateo (2011)
Intel® Cluster Checker (CLCK) is a tool that verifies the configuration, measures performance and validates compliance of the Intel® Cluster Ready Specification in Linux-based clusters. With more than 100 tests-modules CLCK performs a wide range of cluster evaluations. It assesses firmware, kernel, storage, and network settings and also stresses compute nodes and network using multiple benchmarks. Customized checks can be created and integrated to the execution of the tool though an API provided for that purpose. However, this test modules should be written in Perl* programming language. This work proposes a new component of CLCK called Intel® Cluster Checker Multilanguage API (CLCK_Multilang_API), which allows users and developers to write their tailored test modules in arbitrary programming languages and add them to the execution of the tool. Two example languages, Perl* and Python were used as references for this project. The solution includes some mixing of technologies such as SWIG, native C APIs of each language, and Java Script Object Notation (JSON).